Mechanistic insights into the hepatoprotective properties of Mallotus phillipensis fruit: targeting proinflammatory cytokines and free radicals using isolated compound - Waseem Rizvi; Syed Shariq Naeem; Ompal Singh; Shagufta Moin; Kafil Akhtar; Syed Najmul Hejaz Azmi; Zubair Ahmed Memon; Monowarul Mobin Siddique; Zainul Amiruddin Zakaria; Qamar Uddin Ahmed (Elsevier, 2024)
Ethnopharmacological relevance: Mallotus phillipensis (MP) belongs to the endangered plants of great medicinal value. Widely used in the Ayurvedic healthcare system, parts of the plant which are rich in secondary metabolites are used in the treatment of several diseases like eczema, bronchitis, worm infestation, diabetes, kidney stones, cancer, and malaria. In ethnomedicine, MP has been reported to be traditionally used in the treatment and healing of jaundice and inflammatory conditions in the Ayurveda system. This plant was thus selected to explore its hepatoprotective activity. Objective: This study was undertaken to investigate the protective property of MP and a flavanone i.e. 7,4′- Dihydroxy-3′′,3′′-dimethyl-(5,6-pyrano-2′′-one)-8′′′-(3′′′,3′′′-dimethylallyl)-flavanone (A4) previously identified and obtained from the same plant on CCl4-induced liver injury in animal models to validate the folkloric claims. Traditional medicinal plants have the potential to provide phytoconstituents capable of healing liver cells. In this regard, MP is used in various traditional medicinal systems to treat several diseases. Though it has been studied for its hepatoprotective potential, activity on the isolated compounds is yet to be reported to confirm the active principle. Therefore, the study assessed the hepatoprotective effect of ethyl acetate and methanol extracts and a flavanone isolated from MP fruit extract. Methods: Methanol and ethyl acetate fractions of MP fruits at two different doses (300 mg/kg and 500 mg/kg) and a flavanone (A4-50 mg/kg) isolated from MP were tested for hepatoprotective potential in rats. At 50 mg/kg dosage/ day orally, silymarin was used as a standard drug. The effect on liver enzymes and serum cytokines was also verified in animal models. Histopathology and antioxidant tests were performed on liver tissue. Elemental analysis, 1 H- & 13C NMR, MS, IR and UV spectral data were used to characterize the structure of isolated flavanone (A4).